Consumer Preference Factors in Influencing the Purchase of Milk Candy in the Twinmilk Gemah Ripah Business Unit - sayekti, ayutyas; Ardian, Bimo; Agnia Elfath, Amadea Selma; Fitri Hapsari , Kharisma; Adila, Jihan Zakia (IPB University, 2024)
Twinmilk, a business unit of the Gemah Ripah cooperative in Sukabumi, produces milk candy from milk supplied by its farmer members. Despite its potential, Twinmilk's sales have stagnated, particularly for its milk candy. To address this, the company conducted a consumer behavior analysis. The study aimed to analyze the decision-making process in purchasing, the factors influencing purchasing decisions, and consumer attitudes towards the attributes of Twinmilk’s milk candy. The methods used included descriptive analysis, analysis of factors influencing purchasing decisions, and consumer attitude analysis using the Fishbein multi-attribute model. The analysis revealed five key factors influencing purchasing decisions: psychographics (culture, social class, income), demographics (age, gender, lifestyle), knowledge (motivation, awareness), information sources (family, friends, promotions), and behavior (experience, attitude). The consumer attitude score of 133.64 indicates that Twinmilk’s milk candy is well-regarded, with taste being the most valued attribute. However, improvements in accessibility and promotion are essential priorities for growth.